Politics, Shakespeare, East-Central Europe: Theatrical Border Crossings - Almási, Zsolt; Kujawińska Courtney, Krystyna; Nicolaescu, Mădălina; Škrobánková, Klára; Vyroubalova, Ema; Zaharia, Oana-Alis (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
This essay discusses how productions of Shakespeare’s plays that transcend various geographical, national, and linguistic boundaries have influenced the theatrical-political discourse in East-Central Europe in the twenty-first century. It focuses primarily on the work of four internationally-established directors: Andrei Şerban (Romania), Jan Klata (Poland), David Jařab (Czech Republic), and Matei Vișniec (Romania), whose works have facilitated interregional cultural exchange, promoting artistic innovation and experimentation in the region and beyond. Among the boundary-crossing productions analysed in detail are Vișniec’s Richard III will not Take Place, Jařab’s Macbeth – Too Much Blood, Klata’s Measure for Measure, and Serban’s Richard III. The essay also notes that while there has been a relative scarcity of Shakespearean productions in this region engaging closely with gender and race inequalities, productions such as Klata’s African Tales or Vladimír Morávek’s Othello manage to work with these politically charged topics in subtler but still productive ways. The essay concludes that the region’s shared historical experience of totalitarian regimes followed by the struggles of nascent democracies, provides a fertile ground for a diverse and internationally ambitious Shakespearean theatre. The publication of the article was supported by the International Visegrad Fund, project no. 22210007, titled “Crossing Borders with Shakespeare since 1945: Central and Eastern European Roots and Routes.” The project is co-financed by the Governments of the Czechia, Hungary, Poland and Slovakia through Visegrad Grants. The mission of the Fund is to advance ideas for sustainable regional cooperation in Central Europe.